Optimization of solvothermally synthesized ZIF-67 metal organic framework and its application for Cr(VI) adsorption from aqueous solution - N. Mostafazadeh; A.A. Ghoreyshi; K. Pirzadeh (Iranian Journal of Chemical Engineering)
In this study, ZIF-67 was synthesized through solvothermal method to remove Cr(VI) ions from aqueous solution. To improve the structural properties of ZIF-67 and its adsorption capacity, optimization of the synthesis conditions was carried out based on maximum Cr(VI) uptake. From experiments, the optimum condition was revealed as solvent: metal ion molar ratio of 4.6:1, ligand: metal ion molar ratio of 318:1 and temperature of 23℃. The physio-chemical properties of as-synthesized ZIF-67 were investigated by BET, XRD, FTIR and FESEM analyses. Effect of adsorption pH, adsorbent dosage, initial concentration and contact time on adsorption process was investigated. Based on the results, the maximum adsorption capacity of Cr(VI) was 26.27 mg/g which was obtained at 35℃, pH= 5, adsorbent dosage of 3 g/l and initial concentration of 107.82 mg/l. The equilibrium time for Cr(VI) adsorption varied from 180 min for low initial concentration of 9 mg/L to 240 min for a high initial concentration of 90 mg/L. For the synthesized ZIF-67, maximum uptake capacity was reported 26.27 mg/g at initial concentration of 107.82 mg/l. The equilibrium data were described better by Langmuir-Freundlich isotherm model than the other models at three different temperatures. Pseudo-second-order model fitted the experimental data better than pseudo-first-order one. Adsorption thermodynamics indicated that the adsorption process was endothermic and spontaneous in nature. The regenerability of ZIF-67 was also studied in three sequential cycles and the Cr(VI) adsorption was almost retained after two cycles.